Antibody-independent effector mechanisms in resistance to the intestinal nematode parasite Trichuris muris. - Else, K J (1996)
The development of a strong Th2-type immune response is essential in resistance to the intestinal nematode parasite Trichuris muris. Although the underlying cell-regulatory mechanisms important in protective immunity are well defined, the actual Th2-controlled effector mechanisms culminating in worm expulsion are uncharacterized. Using methodology involving the selective reconstitution of severe combined immunodeficiency mice with highly pure populations of CD4+ T cells from immune BALB/c donors, we show here that antibody is not an essential component in resistance to T. muris. Thus, CD4+ T cells purified from BALB/c donor mice at a time point when Th2 cells are in dominance (days 19 to 21 postinfection) confer resistance to infection on recipient severe combined immunodeficiency mice in the complete absence of an antibody response.